Relationship between the work developed in maximal and submaximal exercise capacity tests and the degree of airflow obstruction in individuals with Chronic Obstructive Pulmonary Disease - Lucas Araújo de Oliveira; Rafael Mesquita; Igor Lopes de Brito; Viviane de Moraes Laburú; Fabio Pitta; Vanessa Suziane Probst (Universidade de São Paulo, 2014)
The aim of this study was to investigate the relationship between the work in two exercise capacity tests, a maximum and a submaximal exercise, and the level of airflow obstruction in patients with Chronic Obstructive Pulmonary Disease (COPD). Fifty-three subjects with COPD (29 men, 70±9 years old, 65±14 kg, forced expiratory volume in the first second [FEV1] 38[31-54]% predicted) had their lung function assessed by spirometry, and maximal and submaximal exercise capacity were evaluated by the Incremental Shuttle Walking test (ISWT) and the 6-Minute Walk Test (6MWT), respectively. The work in the tests was calculated by multiplying the covered distance and the individual's body weight (W). To evaluate the contribution of weight on the developed work, subjects were separated into two groups: higher weight (n=32), and lower weight (n=21). FEV1 correlated with the distance on the ISWT and with the ISWT*W (r=0.43 and r=0.49, respectively; p<0.05 for both). Moreover, the distance on the ISWT correlated with the ISWT*W (r=0.88, p<0.0001). Regarding the 6MWT, it was observed that FEV1 had a weak correlation with the covered distance (r=0.29, p=0.03) and a moderate one with the 6MWT*W (r=0.51, p<0.0001). Moreover, the distance covered in the 6MWT was moderately correlated with the 6MWT*W (r=0.47, p=0.0004). The higher weight group showed worse performance only in the 6MWT compared to the lower weight group (407±85 versus 469±64 meters, respectively; p=0.004). The work on the used exercise tests was similarly related to the level of airflow obstruction. The submaximal test, however, appears to have its performance more influenced by the individuals' body weight.